2003
DOI: 10.1021/bi0341859
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Molecular Structure of Fungal Melanin Using13C Biosynthetic Labeling and Solid-State NMR

Abstract: Melanins are enigmatic pigments found in all biological kingdoms that are associated with a variety of functions, including microbial virulence. Despite being ubiquitous in nature, melanin pigments have long resisted atomic-level structural examination because of their insolubility and amorphous organization. Cryptococcus neoformans is a human pathogenic fungus that melanizes only when provided with exogenous substrate, thus offering a unique system for exploring questions related to melanin structure at the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
74
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 27 publications
13
74
0
Order By: Relevance
“…Tian et al (2003) reported that carbon-near sulphur shows chemical shift at 45–40 ppm and CH 2 carbon–CH 2 –CH(NH 2 )–COOH of tyrosine/DOPA can also be seen around 40–35 ppm in 13 C NMR spectrum which is consistent with our sulphur-containing melanin claim.…”
Section: Discussionsupporting
confidence: 91%
“…Tian et al (2003) reported that carbon-near sulphur shows chemical shift at 45–40 ppm and CH 2 carbon–CH 2 –CH(NH 2 )–COOH of tyrosine/DOPA can also be seen around 40–35 ppm in 13 C NMR spectrum which is consistent with our sulphur-containing melanin claim.…”
Section: Discussionsupporting
confidence: 91%
“…Figure 5 showed the 13 C CP/MAS NMR spectra for natural squid ink melanin and soluble fraction B. Both of the two samples showed similar peaks among three characteristic spectral regions as described in the previously literature for the NMR of the melanin (Adhyaru et al 2003;Tian et al 2003, Jalmi et al 2012: (1)δ10-95 ppm was assigned to aliphatic carbons, which was due to proteinaceous material; (2)δ95-165 ppm was assigned to aromatic carbons, including indole or pyrrole type carbons within the polymer; (3)δ165-200 ppm, carbonyl carbon atoms in amides, carboxylates and quinones, which came from the carbonyl in the oxidized quinone form of DHI and DHICA. More specifically, the signals near~δ30ppm and~δ50ppm were assigned to aliphatic groups which come from dihydroderivatives of DHICA, DHI (Knicker et al 1995;Adhyaru et al 2003;Tian et al 2003;Jalmi et al 2012); the signals near~δ103ppm was suggestive of C-3 of indole nucleus, which was from the anomeric carbon of carbohydrates; the peak near~δ130ppm was assigned to aromatic group; the signal near~δ174ppm was due to carbonyl group present as carboxylic acid group, which was derived from DHICA, and the degradation products of DHI and DHICA.…”
Section: Nmr Spectrumsupporting
confidence: 65%
“…The morphological variation of melanin assembly in different wood substrates reported in this research might explain the various chemical structures previously reported for fungal melanin [33,[39][40][41] as well as for the multiple genes identified in melanin biogenesis [21,[42][43][44][45]. Melanin deposits produced in vitro by T. versicolor in sugar maple tended to be attached to the wood cell walls, while in the same substrate pretreated with catechol, those bindings seemed sparse (Fig.…”
Section: Discussionsupporting
confidence: 60%